Interaction potentials for modelling GaN precipitation and solid state polymorphism - Wonglakhon, Tanakorn; Zahn, Dirk (Journal of Physics: Condensed Matter, 2020)
We outline a molecular mechanics model for the interaction of gallium and nitride ions ranging from small complexes to nanoparticles and bulk crystals. While the current GaN force fields allow the modelling of either bulk crystals or single ions dispersed in solution, our model covers both and hence paves the way to describing aggregate formation and crystal growth processes from molecular simulations. The key to this is the use of formal +3 and -3 charges on the gallium and nitride ions, whilst accounting for the charge transfer in GaN crystals by means of additional potential energy terms. The latter are fitted against experimental data of GaN in the wurtzite structure and benchmarked for the zinc-blende and rock-salt polymorphs. Comparison to quantum chemical references and experiment shows reasonable agreement of structures and formation energy of [GaN]n aggregates, elastic properties of the bulk crystal, the transition pressure of the wurtzite to rock-salt transformation and intrinsic point defects. Furthermore, we demonstrate force field transferability towards the modelling of GaN nanoparticles from simulated annealing runs.
CRIS-Team Scopus Importer:2020-03-31